A New Model for a Non-Linear Electromagnetic Model with Self-Interacting Photons - Doria, Renato; Helayel, J.; Chaichian, M.; Spallucci, E.; Cantcheff, M. Botta; Shabad, A. (JOURNAL OF ADVANCES IN PHYSICS, 2015)
A new electromagnetism is still expected to be developed. Thus, under such a principle where nature works as a group, an electromagnetism beyond Maxwell is studied. It considers that light metric antecedes electric charge for founding the EM phenomena. Based on wholeness principle, Lorentz group and gauge invariance this electromagnetism sticked on light is proposed. Then, by electromagnetism it will be understood the physics derived from Lorentz group potential fields family (for simplicity other fields are not included). New electromagnetic fields, sectors, layers and regimes are developed. It yields a branch with transversal and longitudinal EM fields, granular and collective sectors, I-fields layers and four regimes (photonic, massive,neutral, charged) connected through a global photon. Their relationships are determined by a state equation identified as Global Maxwell equation. It contains new Gauss and Ampere laws, exclusive Faraday law for polarization and magnetization vectors, divergenceless magnetization vector having fields as sources, self-interacting photons mediated by a dimensionless coupling constant and other features. It is complemented by a Global Lorentz equation which besides the usual Lorentz force add forces depending on mass and on potential fields.